Fracture management in the polytraumatized patient (Colombia Medica, 1989)
Most patients with multiple injuries are in their best state of health upon admission to the hospital. If they are well resuscitated and stable, they generally tolerate internal fixation and stabilization of all major unstable fractures well within 24 horas of injury.This new surgical attitude reduces the incidence of adult respiratory distress syndrome and the multiple system organic failure and, so far, the mortality, improving the movement of these patients, facilitating nursing care, and permitting early rehabilitation.